High-rate-performance sodium ion battery positive electrode material as well as preparation method and application thereof
By doping Li and Ti elements into the positive electrode material of sodium ion battery, the rate performance and cycle stability of sodium ion battery are improved, and the problems of kinetic slowness and structural instability in the prior art are solved, and high rate performance and high rate performance are achieved The effect of cycle stability.
Patent Information
- Application Number
- CN202411240300.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-27
AI Technical Summary
The current sodium ion battery positive electrode materials have poor rate performance and cyclic stability, mainly due to the kinetic slowness and structural instability of layered transition metal oxides.
Using Li and Ti co-doped nickel manganese tin layered oxide positive electrode material, the phase transition and oxidation reaction are improved by doping Li and Ti elements, the lattice structure is stabilized, the diffusion kinetics and ionic conductivity of Na+ are improved, and the magnification is enhanced. performance.
It significantly improves the rate performance and cycle stability of sodium ion batteries, and has potential application value especially in fast charging solid-state sodium ion batteries.
Smart Images

Figure CN119208584A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical energy storage, and specifically relates to a high-rate performance sodium ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] In order to alleviate the contradiction between the energy crisis of social development and environmental pollution, lithium-ion batteries, as the most important electrochemical energy storage method, have made great progress in the past 20 years. However, with the further large-scale use of lithium-ion batteries in the fields of power batteries and energy storage, the problems of uneven distribution of lithium resources, small reserves and serious premium have become increasingly prominent; therefore, it is urgent to develop the next generation of energy storage systems with excellent electrochemical performance and low prices. Sodium, as a homologous element of lithium, has similar electrochemical properties to lithium ions and can also be used as an ion rocking chair battery. At the same time, sodium-ion batteries have broad application prospects in large-scale energy storage due to their relatively low price and abundant raw material resources, such as natural power generation, solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or large-scale energy storage equipment for communication base stations. So far, the research on sodium ion positive electrode materials is mainly composed of layered transition metal oxides, polyanionic compounds, Prussian blue or Prussian white and their analogs. Among them, the layered transition metal oxide Na x TMO2 has become the material with the greatest potential for large-scale production due to its high specific capacity, good conductivity, environmental friendliness, close to the lithium battery positive electrode process route and easy synthesis. However, problems such as kinetic sluggishness caused by the large radius of sodium ions limit its rate performance. In addition, layered transition metal oxides undergo complex phase changes during the charge and discharge process, which can also cause unstable material structure and poor cycle performance.
[0003] Therefore, improving the diffusion kinetics and cycling stability of layered oxide cathode materials for sodium-ion batteries is an important aspect in improving battery performance. Summary of the invention
[0004] In view of the deficiencies in the prior art, an object of the present invention is to provide a high-rate performance sodium ion battery positive electrode material, wherein the high-rate performance sodium ion battery positive electrode material has a structure in which a P2 phase and an O3 phase coexist.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned high-rate performance sodium ion battery positive electrode material.
[0006] Another object of the present invention is to provide an application of the above-mentioned high-rate performance sodium ion battery positive electrode material in a sodium ion battery.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] A high-rate performance sodium ion battery cathode material, the general structural formula of which is Na 0.7 Ni 0.3 Mn 0.6 Sn 0.03 Li x Ti y O2, where 0 <x<0.07,0<y<0.07,x+y=0.07。
[0009] As a preference, 0.03 <x<0.06,0.01<y<0.04,x+y=0.07。
[0010] As a further preferred option, 0.04 <x<0.06,0.01<y<0.03,x+y=0.07。
[0011] Most preferably, x=0.05 and y=0.02.
[0012] The method for preparing the above-mentioned high-rate performance sodium ion battery positive electrode material comprises the following steps:
[0013] Step 1, mixing a Na source, a Ni source, a Mn source, a Sn source, a Li source and a Ti source until uniform, to obtain a first substance, wherein the ratio of Na in the Na source, Ni in the Ni source, Mn in the Mn source, Sn in the Sn source, Li in the Li source and Ti in the Ti source is 0.735:0.3:0.6:0.03:1.05x:y in terms of the amount of the substances;
[0014] In step 1, the Na source is sodium carbonate.
[0015] In step 1, the Ni source is nickel oxide.
[0016] In step 1, the Mn source is one of manganese carbonate and manganese oxide.
[0017] In step 1, the Sn source is tin dioxide.
[0018] In step 1, the Li source is one of lithium carbonate and lithium hydroxide.
[0019] In step 1, the Ti source is titanium dioxide.
[0020] In step 1, Na source, Ni source, Mn source, Sn source, Li source and Ti source are mixed and ball-milled to be uniform.
[0021] In the above technical solution, the rotation speed of the ball mill is 300 to 1400 rpm, and the ball milling time is 0.5 to 12 hours.
[0022] Step 2: sintering the first substance at 900-1000° C. for 1-12 hours in an air atmosphere, and cooling the furnace to obtain a high-rate performance sodium ion battery positive electrode material.
[0023] Application of the above-mentioned high-rate performance sodium-ion battery positive electrode material in sodium-ion batteries.
[0024] In the above technical solution, the sodium ion battery includes a liquid sodium ion battery and a solid sodium ion battery.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The high-rate performance sodium ion battery positive electrode material of the present invention is a Li and Ti co-doped nickel-manganese-tin layered oxide positive electrode material, which uses Ni, Mn and Sn as the basic framework (Ni and Mn are active elements, which contribute to capacity through their valence changes; and Sn is an inactive element, which is mainly used to stabilize the phase lattice structure), and is doped with Li and Ti elements, wherein the doping of Li elements (Li has a radius that is not much different from that of sodium ions or is similar to the chemical state of sodium ions) can improve or inhibit the occurrence of phase change, and react with oxygen to inhibit the overflow of oxygen and reduce volume change; the doping of Ti elements (Ti has a larger diameter, and its ion radius is larger than that of sodium ions) can increase the interlayer spacing, play a supporting role, and is used to stabilize the lattice and improve the Na + The diffusion dynamics and ionic conductivity of Na + The diffusion rate of Li and Ti is increased and the structural stability is improved, thereby improving the rate performance and maintaining good capacity and cycle performance at high voltage. The synergistic effect of Li and Ti co-doping significantly improves the rate performance and cycle stability of sodium ion batteries. The sodium ion battery prepared from the high-rate performance sodium ion battery positive electrode material of the present invention has both high-rate performance and high cycle stability, and has potential application value in sodium ion batteries, especially fast-charging solid-state sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the XRD pattern of the high rate performance sodium ion battery positive electrode material prepared in Example 1;
[0028] Figure 2 The charge and discharge curve of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 1 at a current density of 0.2C;
[0029] Figure 3 The cyclic voltammogram of the sodium ion battery prepared from the high rate performance sodium ion battery positive electrode material of Example 1 at a current density of 0.5C;
[0030] Figure 4The cyclic voltammogram of the sodium ion battery prepared from the high rate performance sodium ion battery positive electrode material of Example 1 at a current density of 1C;
[0031] Figure 5 The rate diagram of the sodium ion battery prepared from the high rate performance sodium ion battery positive electrode material of Example 1 at different current densities;
[0032] Figure 6 This is the XRD pattern of the high rate performance sodium ion battery positive electrode material prepared in Example 2;
[0033] Figure 7 The charge and discharge curve of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 2 at a current density of 0.2C;
[0034] Figure 8 The cyclic voltammogram of the sodium ion battery prepared from the high rate performance sodium ion battery positive electrode material of Example 2 at a current density of 0.5C;
[0035] Fig. 9 The cyclic voltammogram of the sodium ion battery prepared from the high rate performance sodium ion battery positive electrode material of Example 2 at a current density of 1C;
[0036] Fig.10 The rate diagram of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 2 at different current densities;
[0037] Fig.11 This is the XRD pattern of the high rate performance sodium ion battery positive electrode material prepared in Example 3;
[0038] Fig.12 The charge and discharge curve of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 3 at a current density of 0.2C;
[0039] Fig.13 The cyclic voltammogram of the sodium ion battery prepared from the high rate performance sodium ion battery positive electrode material of Example 3 at a current density of 0.5C;
[0040] Fig.14 The cyclic voltammogram of the sodium ion battery prepared from the high rate performance sodium ion battery positive electrode material of Example 3 at a current density of 1C;
[0041] Fig.15 The rate diagram of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 3 at different current densities;
[0042] Fig.16This is a SEM image of the high-rate performance sodium ion battery positive electrode material prepared in Example 3;
[0043] Fig.17 This is the XRD pattern of the high rate performance sodium ion battery positive electrode material prepared in Example 4;
[0044] Fig.18 The charge and discharge curve of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 4 at a current density of 0.2C;
[0045] Fig.19 The cyclic voltammogram at 0.5C current density of the sodium ion battery prepared from the high rate performance sodium ion battery positive electrode material of Example 4;
[0046] Fig. 20 The cyclic voltammogram at 1C current density of the sodium ion battery prepared from the high rate performance sodium ion battery positive electrode material of Example 4;
[0047] Fig.21 The rate diagram of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 4 at different current densities;
[0048] Fig. 22 XRD diagram of the high-rate performance sodium ion battery positive electrode material prepared in Comparative Example 1;
[0049] Fig.23 The charge and discharge curve of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Comparative Example 1 at a current density of 0.2C;
[0050] Fig.24 The cyclic voltammogram of the sodium ion battery prepared from the high rate performance sodium ion battery positive electrode material of Comparative Example 1 at a current density of 0.5C;
[0051] Fig.25 The cyclic voltammogram of the sodium ion battery prepared from the high rate performance sodium ion battery positive electrode material of Comparative Example 1 at a current density of 1C;
[0052] Fig.26 The rate diagram of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Comparative Example 1 at different current densities;
[0053] Fig. 27 This is a SEM image of the high-rate performance sodium ion battery positive electrode material prepared in Comparative Example 1;
[0054] Fig.28 The charge and discharge curve of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Comparative Example 2 at a current density of 0.2C;
[0055] Fig.29 The cyclic voltammogram of the sodium ion battery prepared from the high rate performance sodium ion battery positive electrode material of Comparative Example 2 at a current density of 0.5C;
[0056] Fig.30 The cyclic voltammogram at 1C current density of the sodium ion battery prepared from the high rate performance sodium ion battery positive electrode material of Comparative Example 2;
[0057] Fig.31 The rate diagram of the sodium ion battery prepared from the high rate performance sodium ion battery positive electrode material of Comparative Example 2 at different current densities;
[0058] Fig.32 The charge and discharge curve of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Comparative Example 3 at a current density of 0.2C;
[0059] Fig.33 The cyclic voltammogram of the sodium ion battery prepared from the high rate performance sodium ion battery positive electrode material of Comparative Example 3 at a current density of 1C;
[0060] Fig.34 This is a rate diagram of a sodium ion battery prepared from the high rate performance sodium ion battery positive electrode material of Comparative Example 3 at different current densities. DETAILED DESCRIPTION
[0061] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0062] The raw material information involved in the following examples is as follows:
[0063] Diaphragm: Whatman glass fiber diaphragm D1823-025;
[0064] Na source (sodium carbonate) was purchased from Fuchen (Tianjin) Chemical Reagent Co., Ltd., and Ni source (nickel oxide), Mn source (manganese carbonate), Sn source (tin dioxide), Li source (lithium carbonate) and Ti source (titanium dioxide) were purchased from MacLean Reagent.
[0065] The various performance indicators in the following examples are strictly measured using precise instruments or standard test methods:
[0066] The crystal structure (XRD pattern) of the samples was determined by X-ray diffractometer (ARL EQUINOX 3000, Thermo Fisher Scientific) at 40 kV and 40 mA with a 2θ range of 10 to 80°.
[0067] The constant current charge / discharge performance tests (cycle performance and rate performance) were performed by an automatic battery tester system (LandCT2001A, China) at a constant temperature of 25 °C and 2.0-4.2 V.
[0068] Embodiments 1 to 4
[0069] A method for preparing a high-rate performance sodium ion battery positive electrode material comprises the following steps:
[0070] Step 1, mixing a Na source, a Ni source, a Mn source, a Sn source, a Li source and a Ti source in a ball mill, and high-energy ball milling at a speed of 1400 rpm for 2 hours until uniform (with acetone as a ball milling medium), to obtain a first substance, wherein the ratio of Na in the Na source, Ni in the Ni source, Mn in the Mn source, Sn in the Sn source, Li in the Li source and Ti in the Ti source is X, and the value of X is shown in Table 1, the Na source is sodium carbonate, the Ni source is nickel oxide, the Mn source is manganese carbonate, the Sn source is tin dioxide, the Li source is lithium carbonate, and the Ti source is titanium dioxide;
[0071] Step 2: placing the first substance in a muffle furnace, heating it to 900° C. at a rate of 5° C. / min in an air atmosphere, sintering it at 900° C. for 12 hours, and cooling it in the furnace to obtain a high-rate performance sodium ion battery positive electrode material.
[0072] Table 1
[0073] Example X serial number Example 1 0.735:0.3:0.6:0.03:0.0315:0.04 <![CDATA[Na 0.7 Ni 0.3 Mn 0.6 Sn 0.03 Li 0.03 You 0.04 O2]]> Example 2 0.735:0.3:0.6:0.03:0.042:0.03 <![CDATA[Na 0.7 Ni 0.3 Mn 0.6 Sn 0.03 Li 0.04 You 0.03 O2]]> Example 3 0.735:0.3:0.6:0.03:0.0525:0.02 <![CDATA[Na 0.7 Ni 0.3 Mn 0.6 Sn 0.03 Li 0.05 You 0.02 O2]]> Example 4 0.735:0.3:0.6:0.03:0.063:0.01 <![CDATA[Na 0.7 Ni 0.3 Mn 0.6 Sn 0.03 Li 0.06 You 0.01 O2]]>
[0074] In Examples 1 to 4, the doping amounts of Li and Ti are not high, which will not change the phase structure of the material and affect the specific capacity of the material.
[0075] Comparative Example 1
[0076] A high-rate performance sodium-ion battery cathode material (Na 0.7 Ni 0.37 Mn 0.6 Sn 0.03 O2) preparation method, comprising the following steps:
[0077] Step 1, mixing a Na source, a Ni source, a Mn source and a Sn source, and high-energy ball milling at a rotation speed of 1400 rpm for 2 hours until uniform (using acetone as a ball milling medium) to obtain a substance A, wherein the ratio of Na in the Na source, Ni in the Ni source, Mn in the Mn source and Sn in the Sn source is 0.735:0.37:0.6:0.03 in terms of the amount of the substance, the Na source is sodium carbonate, the Ni source is nickel oxide, the Mn source is manganese carbonate, and the Sn source is tin dioxide;
[0078] Step 2: Place material A in a muffle furnace, heat to 900° C. at a rate of 5° C. / min in an air atmosphere, sinter at 900° C. for 12 hours, and cool in the furnace to obtain a high-rate performance sodium ion battery positive electrode material.
[0079] Comparative Example 2
[0080] A high-rate performance sodium-ion battery cathode material (Na 0.7 Ni 0.32 Mn 0.6 Sn 0.03 Li 0.05 O2) preparation method, comprising the following steps:
[0081] Step 1, mixing a Na source, a Ni source, a Mn source, a Sn source and a Li source, and high-energy ball milling at a rotation speed of 1400 rpm for 2 hours until uniform (using acetone as a ball milling medium) to obtain a substance B, wherein the ratio of Na in the Na source, Ni in the Ni source, Mn in the Mn source, Sn in the Sn source and Li in the Li source is 0.735:0.32:0.6:0.03:0.0525 in terms of the amount of the substance, the Na source is sodium carbonate, the Ni source is nickel oxide, the Mn source is manganese carbonate, the Sn source is tin dioxide, and the Li source is lithium carbonate;
[0082] Step 2: Place material B in a muffle furnace, heat to 900° C. at a rate of 5° C. / min in an air atmosphere, sinter at 900° C. for 12 hours, and cool in the furnace to obtain a high-rate performance sodium ion battery positive electrode material.
[0083] Comparative Example 3
[0084] A high-rate performance sodium-ion battery cathode material (Na 0.7 Ni 0.32 Mn 0.6 Sn 0.03 Ti 0.02 O2) preparation method, comprising the following steps:
[0085] Step 1, mixing a Na source, a Ni source, a Mn source, a Sn source and a Ti source, and high-energy ball milling at a rotation speed of 1400 rpm for 2 hours until uniform (with acetone as a ball milling medium), to obtain a C substance, wherein the ratio of Na in the Na source, Ni in the Ni source, Mn in the Mn source, Sn in the Sn source and Ti in the Ti source is 0.735:0.32:0.6:0.03:0.02 in terms of the amount of the substance, the Na source is sodium carbonate, the Ni source is nickel oxide, the Mn source is manganese carbonate, the Sn source is tin dioxide, and the Ti source is titanium oxide;
[0086] Step 2: Place the C material in a muffle furnace, heat it to 900° C. at a rate of 5° C. / min in an air atmosphere, sinter it at 900° C. for 12 hours, and cool it in the furnace to obtain a high-rate performance sodium ion battery positive electrode material.
[0087] Examples 5 to 8 and Comparative Examples 4 to 6
[0088] A sodium ion battery (CR2032 coin-type battery, button-type half-cell), comprising: a positive electrode, a counter electrode, a reference electrode, a diaphragm and an electrolyte, wherein the counter electrode and the reference electrode are metal sodium sheets, the diaphragm is an 1823 film, the electrolyte in the electrolyte is NaClO4, and the concentration of the electrolyte in the electrolyte is 1 mol L -1 The solvents in the electrolyte are propylene carbonate (PC) and fluoroethylene carbonate (FEC), and the ratio of propylene carbonate (PC) to fluoroethylene carbonate (FEC) is 95:5 by volume. The method for preparing the positive electrode is as follows: the positive electrode material, the binder solution and the conductive additive (acetylene black) are mixed until uniform to obtain a slurry, the slurry is coated on a carbon (C) aluminum foil (Dongguan Kelude Experimental Equipment Technology Co., Ltd.), and dried in a vacuum drying oven at 80°C. The discs with a diameter of 12 mm are cut by a cutting machine as the positive electrode (the mass load of the positive electrode (positive electrode material) is 0.9 mg cm -2 ), wherein the binder solution is a mixture of polyvinylidene fluoride (PVDF) and N-methylpyrrolidone, and the concentration of polyvinylidene fluoride in the binder solution is 20 mg mL -1 , the ratio of the positive electrode material, polyvinylidene fluoride and the conductive additive (acetylene black) in the binder solution is 8:1:1 by mass, and the positive electrode material is one of the high-rate performance sodium ion battery positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3. The sodium ion battery was assembled in a circulating argon glove box with a moisture content of less than 0.01 ppm and an oxygen content of less than 0.01 ppm.
[0089] Table 2
[0090]
[0091]
[0092] The high rate performance sodium ion battery positive electrode material of Example 1 was subjected to a powder X-ray diffraction test. Figure 1 As shown, the diffraction pattern of Example 1 proves that it has a layered structure of P2 phase (#27-0751) and O3 phase (#54-0887).
[0093] Figure 2 The charge and discharge curve of the sodium ion battery prepared by the high-rate performance sodium ion battery positive electrode material of Example 1 at a current density of 0.2C is smooth, the charge specific capacity is 119 mA h / g, and the discharge specific capacity is 117 mA h / g.
[0094] like Figure 3As shown, the initial discharge specific capacity of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 1 at a current density of 0.5C is 117mA h / g, and the capacity retention rate after 100 cycles is 99%.
[0095] like Figure 4 As shown, the initial discharge specific capacity of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 1 at a current density of 1C is 107 mA h / g, and the capacity retention rate after 100 cycles is 98%.
[0096] like Figure 5 As shown, the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 1 has a discharge capacity of 126 mA h / g, 126 mA h / g, 123 mA h / g, 119 mA h / g, 112 mA h / g and 102 mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively, and the discharge capacity is 129 mA h / g when returning to 0.1C.
[0097] The high rate performance sodium ion battery positive electrode material of Example 2 was subjected to a powder X-ray diffraction test. Figure 6 As shown, the diffraction pattern of Example 2 proves that it has a layered structure of P2 phase (#27-0751) and O3 phase (#54-0887).
[0098] Figure 7 The charge and discharge curve of the sodium ion battery prepared by the high-rate performance sodium ion battery positive electrode material of Example 2 at a current density of 0.2C is smooth, the charge specific capacity is 132 mA h / g, and the discharge specific capacity is 128 mA h / g.
[0099] like Figure 8 As shown, the initial discharge specific capacity of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 2 at a current density of 0.5C is 131mA h / g, and the capacity retention rate after 100 cycles is 96%.
[0100] like Fig. 9 As shown, the initial discharge specific capacity of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 2 at a current density of 1C is 132 mA h / g, and the capacity retention rate after 100 cycles is 98%.
[0101] like Fig.10As shown, the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 2 has a discharge capacity of 137 mA h / g, 141 mA h / g, 137 mA h / g, 132 mA h / g, 125 mA h / g and 113 mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively, and the discharge capacity is 140 mA h / g when returning to 0.1C.
[0102] The high rate performance sodium ion battery positive electrode material of Example 3 was subjected to a powder X-ray diffraction test. Fig.11 As shown, the diffraction pattern of Example 3 proves that it has a layered structure of P2 phase (#27-0751) and O3 phase (#54-0887).
[0103] Fig.12 The charge and discharge curve of the sodium ion battery prepared by the high-rate performance sodium ion battery positive electrode material of Example 3 at a current density of 0.2C is smooth, the charge specific capacity is 152 mA h / g, and the discharge specific capacity is 146 mA h / g.
[0104] like Fig.13 As shown, the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 3 has an initial discharge specific capacity of 150 mA h / g at a current density of 0.5 C, and the capacity retention rate after 100 cycles is 90%.
[0105] like Fig.14 As shown, the initial discharge specific capacity of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 3 at a current density of 1C is 146 mA h / g, and the capacity retention rate after 100 cycles is 95%.
[0106] like Fig.15 As shown, the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 3 has a discharge capacity of 148 mA h / g, 151 mA h / g, 147 mA h / g, 141 mA h / g, 130 mA h / g, 115 mA h / g, 96 mA h / g and 81 mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C and 20C, respectively, and the discharge capacity is 147 mA h / g when returning to 0.1C.
[0107] Fig.16 This is a SEM image of the high-rate performance sodium ion battery positive electrode material prepared in Example 3. Fig.16 As shown, the positive electrode material of the high-rate sodium-ion battery has a layered structure.
[0108] The high rate performance sodium ion battery positive electrode material of Example 4 was subjected to a powder X-ray diffraction test. Fig.17 As shown, the diffraction pattern of Example 4 proves that it has a layered structure of P2 phase and O3 phase.
[0109] Fig.18 The charge and discharge curve of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 4 at a current density of 0.2C is smooth, the charge specific capacity is 139 mA h / g, and the discharge specific capacity is 129 mA h / g.
[0110] like Fig.19 As shown, the initial discharge specific capacity of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 4 at a current density of 0.5C is 128mA h / g, and the capacity retention rate after 100 cycles is 95%.
[0111] like Fig. 20 As shown, the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 4 has an initial discharge specific capacity of 115 mA h / g at a current density of 1C, and a capacity retention rate of 93% after 100 cycles.
[0112] like Fig.21 As shown, the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Example 4 has a discharge capacity of 132 mA h / g, 124 mA h / g, 114 mA h / g, 105 mA h / g, 102 mA h / g and 80 mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively, and the discharge capacity is 118 mA h / g when returning to 0.1C.
[0113] The high rate performance sodium ion battery positive electrode material of Comparative Example 1 was subjected to a powder X-ray diffraction test. Fig. 22 As shown, the diffraction pattern of Comparative Example 1 proves that it has a layered structure of P2 phase and O3 phase.
[0114] Fig.23 This is a charge and discharge curve diagram of a sodium ion battery prepared from the high-rate performance sodium ion battery positive electrode material of Comparative Example 1 at a current density of 0.2C. The charge and discharge curve presents multiple steps, proving that the high-rate performance sodium ion battery positive electrode material of Comparative Example 1 is not a solid solution reaction.
[0115] like Fig.24 As shown, the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Comparative Example 1 has an initial discharge specific capacity of 171 mA h / g at a current density of 0.5C, and a capacity retention rate of 57% after 100 cycles.
[0116] like Fig.25 As shown, the initial discharge specific capacity of the sodium ion battery prepared by the high-rate performance sodium ion battery positive electrode material of Comparative Example 1 is 131 mA h / g at a current density of 1C, and the capacity retention rate is 77% after 100 cycles.
[0117] like Fig.26 As shown, the discharge specific capacities of the sodium ion battery prepared from the high-rate performance sodium ion battery positive electrode material of Comparative Example 1 at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C are 202mA h / g, 151mA h / g, 116mA h / g, 104mA h / g, 96mA h / g and 84mA h / g, respectively. The capacity of the sodium ion battery prepared from the high-rate performance sodium ion battery positive electrode material of Comparative Example 1 decays rapidly at different current densities.
[0118] Fig. 27 This is a SEM image of the high-rate performance sodium ion battery positive electrode material prepared in Comparative Example 1. The high-rate performance sodium ion battery positive electrode material prepared in Comparative Example 1 is uneven in size.
[0119] Fig.28 The charge and discharge curve of the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Comparative Example 2 at a current density of 0.2C is shown, with a charge specific capacity of 148 mA h / g and a discharge specific capacity of 144 mA h / g.
[0120] like Fig.29 As shown, the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Comparative Example 2 has an initial discharge specific capacity of 145 mA h / g at a current density of 0.5 C, and a capacity retention rate of 90% after 100 cycles.
[0121] like Fig.30 As shown, the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Comparative Example 2 has an initial discharge specific capacity of 134 mA h / g at a current density of 1C, and a capacity retention rate of 92% after 100 cycles.
[0122] like Fig.31 As shown, the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Comparative Example 2 has a discharge specific capacity of 143 mA h / g, 135 mA h / g, 127 mAh / g, 119 mA h / g and 105 mA h / g at current densities of 0.2C, 0.5C, 1C, 2C and 5C, respectively, and the discharge specific capacity at each current density is lower than that of the embodiment.
[0123] Fig.32The charge and discharge curve of the sodium ion battery prepared by the high-rate performance sodium ion battery positive electrode material of Comparative Example 3 at a current density of 0.2C is shown. The charge and discharge curve presents multiple steps, proving that it is not a solid solution reaction. The charge specific capacity is 188 mA h / g, and the discharge specific capacity is 179 mA h / g.
[0124] like Fig.33 As shown, the sodium ion battery prepared by the high rate performance sodium ion battery positive electrode material of Comparative Example 3 has an initial discharge specific capacity of 122 mA h / g at a current density of 1C, and a capacity retention rate of 80% after 100 cycles.
[0125] like Fig.34 As shown, the discharge specific capacities of the sodium ion battery prepared by the high-rate performance sodium ion battery positive electrode material of Comparative Example 3 at current densities of 0.2C, 0.5C, 1C, 2C and 5C are 154mA h / g, 115mA h / g, 111mAh / g, 102mA h / g and 93mA h / g, respectively. Compared with the embodiment, the capacity of the sodium ion battery prepared by the high-rate performance sodium ion battery positive electrode material of Comparative Example 3 decays rapidly at different current densities.
[0126] Figure 4 , Fig. 9 , Fig.14 , Fig. 20 and Fig.25 The long cycle diagrams of the sodium ion batteries prepared by Examples 1 to 4 and Comparative Example 1 at 2.0-4.2V and 1C are respectively Figure 4 , Fig. 9 , Fig.14 , Fig. 20 and Fig.25 By comparison, it can be seen that the capacity retention rate of the sodium ion batteries prepared by Examples 1 to 4 is significantly improved compared with that of Comparative Example 1.
[0127] Figure 5 , Fig.10 , Fig.15 , Fig.21 and Fig.26 The rate performance diagrams of the sodium ion batteries prepared by Examples 1 to 4 and Comparative Example 1 at 2.0-4.2V and different current densities are shown in FIG. Figure 5 , Fig.10 , Fig.15 , Fig.21 and Fig.26 By comparison, it can be seen that the rate performance of the sodium ion batteries prepared in Examples 1 to 4 is significantly improved compared with that in Comparative Example 1.
[0128] The performance of the embodiments and comparative examples are summarized and analyzed in combination with Table 3 and Table 4, proving that co-doping of Li and Ti can significantly improve the rate performance and cycle stability of sodium ion batteries.
[0129] Table 3 (obtained from the magnification diagram)
[0130]
[0131] Table 4 (obtained from cyclic voltammogram)
[0132]
[0133]
[0134] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A high rate performance sodium ion battery positive electrode material, characterized in that: Its general structural formula is Na 0.7 Ni 0.3 Mn 0.6 Sn 0.03 Li x Ti y O2, where 0 <x<0.07,0<y<0.07,x+y=0.07。 2. The method for preparing a high-rate performance sodium ion battery positive electrode material according to claim 1, characterized in that: The following steps are involved: Step 1, mixing a Na source, a Ni source, a Mn source, a Sn source, a Li source and a Ti source until uniform, to obtain a first substance, wherein the ratio of Na in the Na source, Ni in the Ni source, Mn in the Mn source, Sn in the Sn source, Li in the Li source and Ti in the Ti source is 0.735:0.3:0.6:0.03:1.05x:y in terms of the amount of the substances; Step 2: sintering the first substance at 900-1000° C. for 1-12 hours in an air atmosphere, and cooling the furnace to obtain a high-rate performance sodium ion battery positive electrode material.
3. A high-rate performance sodium ion battery positive electrode material, characterized in that: Its structural formula is Na 0.7 Ni 0.32 Mn 0.6 Sn 0.03 Li 0.05 O2.
4. The method for preparing a high-rate performance sodium ion battery positive electrode material according to claim 3, characterized in that: The following steps are involved: Step 1, mixing a Na source, a Ni source, a Mn source, a Sn source and a Li source until uniform, to obtain a substance B, wherein the ratio of Na in the Na source, Ni in the Ni source, Mn in the Mn source, Sn in the Sn source and Li in the Li source is 0.735:0.32:0.6:0.03:0.0525 in terms of the amount of the substances; Step 2: sintering the substance B at 900-1000° C. for 1-12 hours in an air atmosphere, and cooling the furnace to obtain a high-rate performance sodium ion battery positive electrode material.
5. Use of the high-rate performance sodium ion battery positive electrode material as claimed in claim 1 or 2 in a sodium ion battery.
6. The use according to claim 5, characterized in that: The sodium ion battery includes a liquid sodium ion battery and a solid sodium ion battery.
7. The use according to claim 5, characterized in that: The sodium ion battery prepared from high-rate performance sodium ion battery positive electrode material has a charging capacity of up to 152 mA h / g at a current density of 0.2C, and a discharge capacity of up to 146 mA h / g.
8. The use according to claim 5, characterized in that: The sodium ion battery prepared from the high-rate performance sodium ion battery positive electrode material has an initial discharge specific capacity of up to 150 mA h / g at a current density of 0.5C, and a capacity retention rate of up to 90% after 100 cycles.
9. The use according to claim 5, characterized in that: The sodium ion battery prepared from high-rate performance sodium ion battery positive electrode material has an initial discharge specific capacity of up to 146 mA h / g at a current density of 1C, and a capacity retention rate of up to 95% after 100 cycles.
10. The use according to claim 5, characterized in that: The sodium ion battery prepared from the high-rate performance sodium ion battery positive electrode material has a discharge specific capacity of up to 148mA h / g, 151mA h / g, 147mA h / g, 141mA h / g, 130mA h / g, 115mA h / g, 96mA h / g and 81mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C and 20C, respectively.
Citation Information
Cited By
Preparation and application of layered oxide positive electrode material of high-rate sodium-ion battery
CN121237869A
